A Change in the Supply of Professionals in the Health Care Sector and Assessment of the Demand for Physicians and Opportunities for their Integration into the Labour Market - Pocius, Arūnas (Lithuanian Journal of Statistics, 2013)
The article paper analyses the supply of health care professionals in health care sector in Lithuania in terms of demographic change. On the basis of data from different studies and of the analysis carried out in this work by the author, particular attention is given to the problem of the assessment of the demand for health care professionals (physicians) in health care sector in Lithuania. When analysing the integration of health care professionals into the labour market, in addition to sociological surveys, the data of Lithuanian Statistics Lithuania Department on labour force (employment) was were used. This paper investigates explores the possibility of using different data sources for the analysis of the demand for health care professionals (physicians), as well as analyses their situation in the labour market on the basis of the scientific literature review.
Keywords: labour market; integration of physicians doctors; demand of for physicians doctors; labour migration; employment; specialists; sociological surveys